Modeling chlordecone toxicokinetics data in growing pigs using a nonlinear mixed-effects approach. (July 2020) - Fourcot, A.; Feidt, C.; Bousquet-Mélou, A.; Ferran, A.A.; Gourdine, J.L.; Bructer, M.; Joaquim-Justo, C.; Rychen, G.; Fournier, A.
Abstract: The use of chlordecone (CLD), a chlorinated polycyclic pesticide used in the French West Indies banana fields between 1972 and 1993, resulted in a long-term pollution of agricultural areas. It has been observed that this persistent organic pollutant (POP) can transfer from contaminated soils to food chain. Indeed, CLD is considered almost fully absorbed after involuntary ingestion of contaminated soil by outdoor reared animals. The aim of this study was to model toxicokinetics (TKs) of CLD in growing pigs using both non-compartmental and nonlinear mixed-effects approaches (NLME). In this study, CLD dissolved in cremophor was intravenously administrated to 7 Creole growing pigs and 7 Large White growing pigs (1 mg kg −1 body weight). Blood samples were collected from time t = 0 to time t = 84 days. CLD concentrations in serum were measured by GCMS/MS. Data obtained were modeled using Monolix (2019R). Results demonstrated that a bicompartmental model best described CLD kinetics in serum. The influence of covariates (breed, initial weight and average daily gain) was simultaneously evaluated and showed that average daily gain is the main covariate explaining inter-individual TKs parameters variability. Body clearance was of 76.7 mL kg −1 d −1 and steady-state volume of distribution was of 6 L kg −1 . This modeling approach constitutes the first application of NLME to study CLD TKs in farm animals and will be further used for rearing management practices in contaminated areas. Highlights: Non-linear mixed effects model to study chlordecone toxicokinetics in pigs. Body clearance in growing pigs is 76.7 ± 3.2 mL kg −1 d −1 . Distribution volume in growing pigs is 6.0 ± 0.3 L kg −1 . Inter-individual variability can be explained by average daily gain.